Posisi Daya Saing Perusahaan Taksi Blue Bird pada Era Teknologi Disruptif - Victor Agustinus (Universitas Tarumanagara, 2022)
The number of internet user in Indonesia is increasing significantly. In Indonesia, internet is not only accesed by PC but also smartphone. Therefore, new companies with new business models which utilize the internet connected smartphone is popping up nowaday. Those newcomers are serious threats to existing companies. That phenomenon is called disruptive technology. It happens to all industries including taxi services. Today, conventional taxi companies are challenged by online taxi companies. This research is aimed to identifying the competitive position of conventional taxi company in macro and micro environment.